Assessment of Heavy Metals and Pesticide Residues in Soils in Adamawa State, Nigeria - Master, Micah Musa; Reuben, Usaku; Fari, Dowell Bartimaeus; Umaru, Mustapha (Darul Yasin Al Sys, 2025)
Pesticides and heavy metals are persistent, non-biodegradable contaminants capable of bioaccumulating through ecological food chains such as soil–plant–food and seawater–marine organism–food pathways. Consequently, accurate monitoring of their concentrations is critical for ensuring environmental and public health safety. This study assessed and monitored the concentrations of heavy metals and pesticide residues in soils from various agricultural sites in Adamawa State, Nigeria. Soil samples were collected from Waja, Shashau, Munga, and Garaha Larh in Hong Local Government Area. Heavy metals were analyzed using Atomic Absorption Spectrophotometry (AAS), while pesticide residues—specifically organochlorine and organophosphate compounds—were identified and quantified using Gas Chromatography-Mass Spectrometry (GC-MS). Organochlorine pesticides detected in the soil included Lindane (2.136 mg/kg), Aldrin (1.022 mg/kg), Heptachlor (0.358 mg/kg), and Dieldrin (0.167 mg/kg), all of which exceeded the Codex Maximum Residue Limits (MRLs). Organophosphate pesticides such as Diazinon (6.133 mg/kg), Dichlorvos (0.848 mg/kg), and Chlorpyrifos (0.215 mg/kg) were also detected, with Diazinon and Dichlorvos exceeding MRLs. Heavy metals identified in soil included Copper (0.630–16.77 mg/kg), Zinc (12.183–246 mg/kg), Lead (3.648–9.056 mg/kg), Cadmium (0.563–3.842 mg/kg), and Chromium (1.784–5.378 mg/kg). In several locations, Cadmium concentrations exceeded permissible limits, indicating localized contamination. The high levels of Lindane and other contaminants are likely due to excessive use of agrochemicals and potential pollution of irrigation water. The findings underscore the urgent need for regulated agrochemical usage, improved irrigation practices, and ongoing environmental monitoring to mitigate health and ecological risks.